Microbial fossil record of rocks from the Ross Desert, Antarctica: implications in the search for past life on Mars - Wierzchos, Jacek; Ascaso, Carmen (International Journal of Astrobiology, 2002)
9 pages, figures, and tables statistics. Cryptoendolithic microbial communities living within Antarctic rocks are an example of survival in an extremely cold and dry environment. The extinction of these micro-organisms formerly colonizing sandstone in the Mount Fleming area (Ross Desert), was probably provoked by the hostile environment. This is considered to be a good terrestrial analogue of the ®rst stage of the disappearance of possible life on early Mars. To date, only macroscopically observed indirect biomarkers of the past activity of cryptoendoliths in Antarctic rocks have been described. The present paper con®rms, for the ®rst time, the existence of cryptoendolith microbial fossils within these sandstone rocks. The novel in situ application of scanning electron microscopy with backscattered electron imaging and simultaneous use of X-ray energy dispersive spectroscopy allowed the clear detection of microfossils left behind by Antarctic endoliths. Careful interpretation of the morphological features of cells, such as preserved cell walls in algae, fungi and bacteria, cytoplasm elements such as chloroplast membranes in algae and organic matter traces, mineral associations, and the spatial context of these structures all point to their identi®cation as cryptoendolith microfossils. This type of investigation will prompt the development of research strategies aimed at locating and identifying the signs that Martian microbiota, probably only bacteria if they existed, may have been left for us to see. Peer reviewed